Pendidikan Islam Ramah Budaya: Pendekatan Filosofis - Muhamad Turmuzi; Fatia Inas (Journal of Islamic Education Research, 2020)
Lately, the emergence of various problems in human life, especially in education. One of the issues or issues that are quite viral in this modern era is the fragility or in other words the shifting of Islamic values about tolerance towards all tribes and cultures. Therefore, the presence of this study aims to examine how the concept of Islamic education in overcoming various human problems or in the term "humanizing humanity" in the sense of Islamic education as a potential transaction process in culture related to specific Islamic values in dealing with ethnic, cultural differences, and various problems of human life, especially in education. By using a philosophical approach which is one branch of philosophy that discusses the nature of human knowledge. His philosophy is similar to Islamic education taught by the Prophet long before his preaching that did not look at ethnicity, religion, culture, and nation.